Sequence of oral manifestations in rhino-maxillary mucormycosis - Bharati R Doni; Basavaraj V Peerapur; Lathadevi Hassan Thotappa; Surekha B Hippargi (Wolters Kluwer Medknow Publications, 2011)
Mucormycosis, caused by saprophytic fungi of the order Mucorales of the class Zygomycetes, is a rare opportunistic fungal infection, which has a rapidly progressive and fulminant course with fatal outcome. These fungi are ubiquitous, found in soil, bread molds, decaying fruits and vegetables. The most common form of mucormycosis is rhinocerebral and is usually seen in uncontrolled diabetes mellitus or in immunocompromised patients. This fungus invades the arteries, leading to thrombosis that subsequently causes necrosis of hard and soft tissues. We report a case of palatal perforation by rhino-maxillary mucormycosis in an immunocompromised patient. The aim of this article is to draw attention to the clinical presentation and pathogenesis of mucormycosis and to emphasize the need for high degree of suspicion in its diagnosis and management.